High Prevalence of Gut Microbiota Colonization with Broad-Spectrum Cephalosporin Resistant Enterobacteriaceae in a Tunisian Intensive Care Unit - Maamar, Elaa; Ferjani, Sana; Jendoubi, Ali; Hammami, Samia; Hamzaoui, Zaineb; Mayonnove-Coulange, Laure; Saidani, Mabrouka; Kammoun, Aouatef; Rehaiem, Amel; Ghedira, Salma; Houissa, Mohamed; Boutiba-Ben Boubaker, Ilhem; et al. (Frontiers in Microbiology, 2016)
Healthcare-associated infections due to cefotaxime-resistant Enterobacteriaceae (CRE) have become a major public health threat, especially in intensive care units (ICUs). Often acquired nosocomially, CRE can be introduced initially by patients at admission. This study aimed to determine the prevalence and genetic characteristics of CRE-intestinal carriage in ICU patients, to evaluate the rate of acquisition of these organisms during hospitalization, and to explore some of the associated risk factors for both carriage and acquisition. Between December 2014 and February 2015, the 63 patients admitted in the ICU of Charles Nicolle hospital were screened for rectal CRE colonization at admission and once weekly thereafter to identify acquisition. CRE fecal carriage rate was 20.63% (13/63) at admission and the acquisition rate was 42.85% (15/35). Overall, 35 CRE isolates were collected from 28 patients (25 Klebsiella pneumoniae, 7 Escherichia coli and 3 Enterobacter cloacae strains). Seven patients were simultaneously colonized with 2 CRE isolates. CTX-M-15 was detected in most of the CRE isolates (30/35, 88.23%).Three strains co-produced CMY-4 and 22 strains were carbapenem-resistant and co-produced a carbapenemase [OXA-48 (n=13) or NDM-1 (n=6)]. All isolates were multidrug resistant. Molecular typing of K. pneumoniae strains, revealed 8 Pulsed field gel electrophoresis (PFGE) patterns and 4 sequence types (ST) [ST101, ST147, ST429 and ST336]. However, E. coli isolates were genetically unrelated and belonged to A (n=2), B1 (n=2) and B2 (n=3) phylogenetic groups and to ST131 (2 strains), ST572 (2 strains), ST615 (one strain) and ST617 (one strain). Five colonized patients were infected by CRE (4 with the same strain identified from their rectal swab and 1 with a different strain). Whether imported or acquired during the stay in the ICU, colonization by CRE is a major risk factor for the occurrence of serious nosocomial infections. Their systematic screening in fecal carriage is mandatory to prevent the spread of these multidrug resistant bacteria.